Learning Patterns of Deaf Students in Islamic Religious Studies - Moh. Irsyad Fahmi MR; Khabibur Rohman (Al Ibtida: Jurnal Pendidikan Guru MI, 2019)
AbstractThis research is intended to learning patterns of deaf students in Islamic Religious Studies (IRS) class at the elementary school level, determine the preparation of students, and identify the factors that support and hinder the learning process. The method used in this research is qualitative, with a case study approach. Data was collected using the interview and documentation approaches. Data analysis involved content analysis. The study finds that deaf students follow traditional learning patterns, in which teachers are equipped with materials, tools, and media that can be used to convey abstract ideas. In such a learning pattern, teachers play the most important role in determining content and methods to enable students to follow the lessons. Factors supporting the learning process include parent concern and teacher cooperation. A major factor hindering the learning process, meanwhile, is students' limited linguistic abilities, as a result of which they have difficulty understanding the lessons.Keywords: deaf, learning patterns, special education.AbstrakPenelitian ini dimaksudkan untuk menguraikan pola pembelajaran siswa tunarungu di kelas Pendidikan Agama Islam (PAI) pada tingkat sekolah dasar, memahami persiapan siswa, dan mengidentifikasi faktor-faktor yang mendukung dan menghambat proses pembelajaran. Metode yang digunakan dalam penelitian ini adalah kualitatif, dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara dan dokumentasi. Analisis data yang digunakan adalah analisis isi. Penelitian ini menemukan bahwa siswa tunarungu masih mengikuti pola pembelajaran tradisional, di mana guru dengan menggunakan bahan, alat, dan media menyampaikan ide-ide abstrak. Dalam pola pembelajaran tersebut guru memainkan peran paling penting dalam menentukan konten dan metode yang memungkinkan siswa untuk mengikuti pelajaran. Faktor pendukung proses pembelajaran meliputi perhatian orang tua dan kerjasama guru. Faktor utama yang menghambat proses belajar adalah kemampuan linguistik siswa yang terbatas, sehingga mereka mengalami kesulitan dalam memahami pelajaran.Kata kunci: tunarungu, pola pembelajaran, pendidikan khusus.